Data management for libraries: understanding DBMS,RDBMS,IR technologies & tools - Suseela,V.J (Ess Ess Publications, 2017)
A library is a system that consists of inter-dependent and interrelated sub-systems that generate huge amounts of data. It shares the common data within the system and across the systems. In modern integrated library systems, the bibliographic data is primarily connected to various other sub-systems. The back-end relational database management systems (RDBMS) are effective in organizing the data in standard formats while avoiding data redundancy. The data created from this process is usually made available to users for their retrieval. Thus, the entire cycle revolves around the growing information requirements of users. This book attempts to focus on creating and understanding the basic concepts of databases, library databases, DBMS/RDBMS functioning at the backend of LIS operations in building such databases while specifying the usefulness of DBMS approach in the effective retrieval of information from library catalogs, as well as from external online databases. The relevant strategies to be applied in information retrieval and useful tools are briefly dealt with, with information given on emerging trends in library data management.